Identifikasi Cacing Soil-Transmitted Helmiths pada Tanah di Desa Bekoso Kalimantan Timur - Nurmansyah, Dian; Zalianty, Firda; Puspawati Puspawati; Muhammad Arsyad; Maya Sasmitha (Lembaga Pengembangan Kinerja Dosen, 2025)
Worm infestation due to Soil-Transmitted Helminths (STH) infection remains a public health problem, especially among elementary school children who frequently interact with contaminated soil. This condition is a major concern because it can cause long-term health problems, particularly in terms of physical growth and development of children. This study aims to identify the presence of STH worm eggs and larvae in soil and fecal samples of children in Bekoso Village, Pasir Belengkong District, Paser Regency, East Kalimantan. This study used a descriptive approach with a cross-sectional design. The samples used consisted of 23 soil points taken from oil palm plantations with sandy and loose soil criteria, as well as 16 fecal samples from elementary school children. Fecal examination was carried out using the Kato-Katz method to detect worm eggs, while the soil was examined using the Baermann technique to detect worm larvae. The results showed that 25% of children's fecal samples were infected with worm eggs, with 12.5% containing hookworm eggs, 12.5% Taenia sp. eggs, and 6.25% Ascaris lumbricoides eggs. In soil samples, 60.87% tested positive for Strongyloides stercoralis larvae and 26.09% tested positive for Ascaris lumbricoides eggs. These findings indicate a high risk of STH infection in children in the area. Environmental factors such as soil moisture, soil texture suitable for worm breeding, and poor personal hygiene practices are suspected to be the main causes of the spread of infection. This study emphasizes the importance of education on clean and healthy living behaviors (PHBS) and improving environmental sanitation to reduce cases of worm infection, especially in endemic areas such as Bekoso Village. More comprehensive prevention efforts are urgently needed to address this problem and improve public health, especially among elementary school children.